Conscientização - Kovic, Mark (Cadernos Brasileiros de Terapia Ocupacional, 2016)
Paulo Freire included this term in Pedagogy of the Oppressed (FREIRE, 2006) to speak to the need for consciousness awareness as a means toward self- realization. The process through which this may occur is interwoven intricately such that the outcome is one in which individuals may move toward a social awareness but also that new procedures and policies may be created. A key aspect of this approach is critical reflexivity – to self-analyze toward self-realization. Critical reflexivity should be linked to a culture, an identity, or a nation. Brazil is a nation with a strong cultural identity which may engage inn and benefit from this dynamic discussion. Paulo Freire poses that it is possible to perceive social, political and economic contradictions, and to take action against the oppressive elements of one’s reality. This may occur through a process of discussion and transformation. Thus, it may be inferred that education, more specifically in this discussion occupational therapy education, must come from a common pedagogy rather than consideration of a tabula rasa to achieve competence. Occupational therapy (OT) is at a unique crossroads through which the profession may reflexively critique itself to move toward achieving awareness such that the profession may meet individual and societal needs. This may be accomplished through a thorough a cohesive definition and understanding of the core of occupation, an appreciation of the historical context of OT in Brazil, and metrics of achievement for stated objectives toward these goals. This is only the beginning of the next steps of the journey. Brazilian occupational therapy may transform itself to embrace the early 21st century needs of its citizens and simultaneously strive toward conscientização from the macroscopic to the mesoscopic to the microscopic levels. The concept of occupation as a core has been discussed by Hooper and colleagues (HOOPER et al., 2014). At the macroscopic level, the challenge and potential benefit of a clear definition of a profession’s core is that once incorporated, this definition can be the impetus for a common language and pedagogy. Hooper and colleagues further pose that this “core subject” may be the foundation for a subject-centered learning model from which this core is linked with and supports educational decisions in a curriculum (HOOPER et al., 2014). Magalhães and Galheigo (2010) share a similar perspective on this matter. These authors learned that although Brazilian occupational therapists have developed skills and knowledge based upon international standards, there is a local influence upon the nuances of how the profession is enacted at the point-of-care. This may translate ineffectively to policy makers, and ultimately may affect how services are validated. These authors also describe that razilian occupational therapists have not been at the center of this consensus of terminology. Additionally, it may be perceived that common “professional language” may be perceived negatively by clients. Yet, common language is crucial for effective communication. McInerney et al. (2007) adds a dimension to this topic in that these authors speak to the cultural sensitivity in Brazil to social inclusion. This, in turn, necessitates professionals, such as occupational therapists, to address this need and facilitate the implementation of models which guide societal values and actions such as Programa Integrando – an integrated, socially inclusive, community-based model. This macro-level approach may be summarized with the concept of habitus. Habitus implies that commonly accepted definitions, terminology, and social inclusion, instead of individual processes, may lead toward actions which endure, are replicable, and may also adjust over time (GALHEIGO, 2011). Emancipation, empowerment, and engagement are potential outcomes of actions taken at the mesoscopic level. A historical perspective of Brazilian occupational therapy allows an opportunity to appreciate the mesoscopic level of the profession as a key transition point to link the macro- and micro- aspects toward a meaningful future. Emmel, Cruz and Figueiredo (2015) identify that occupational therapy was first offered as an undergraduate program as recently as 1969. This followed in the 1970’s with limited opportunities to expand upon knowledge. Legislation facilitated growth in the profession throughout Brazil (LOPES; HAHN, 2004). As growth continued over recent decades, this was paired with establishment of social policies for persons with disabilities in Brazil. Social inclusion became an opportunity for further growth for the profession. Lopes et al. (2012) contributes the rigor of this discussion with an emphasis upon social inclusion experiences to support at-risk persons in Brazilian society. These authors discuss a type of situational learning which fits the social occupational therapy approach seen throughout Brazil. This learning approach is furthered by an overarching intent to support social inclusion, maximize network supports, and minimize exclusion and vulnerability. Malfitano et al. (2014) link Brazilian social occupational therapy to situational experiences in Canada. The concept of territory is emphasized to describe the situational context of social life. These authors describe a variety of strategies and programs which are linked to local, regional, and national policies. In doing so, the link is validated between the macro- and micro- levels within the context of the occupational therapy fabric of Brazil. These various examples frame the robust ethic of the Brazilian social occupational therapy profession. The microscopic level necessitates a common language interwoven with the cultural identity linked to the social occupational therapy history Brazil provide the opportunity for future growth. Such growth may occur with a concerted effort toward sharing this knowledge through rigorous peer-reviewed publication. Brown (2011) discusses the variety of peer-reviewed journal metrics and how these metrics relate to impact factors as well as potential publication within OT journals. Yet he also identifies the reality of these metrics for the foreseeable future and suggests the establishment of an “esteem factor” based upon this analysis. Gutman (2010) analyzed publications in the American Journal of Occupational Therapy in 2010 and suggested that peer-reviewed publication viability must be linked to efficacious and rigorous studies which demonstrate the unique benefit of occupational therapy. Dissemination of knowledge is important, yet, everyday practice has relevance. Schaaf (2015) spoke to a data-driven decision model, which, although applied in the United States of America, may have potential application elsewhere in the world. This process includes eleven steps which provide a systematic means for a practitioner to address client needs. These steps include: identification of participation needs, description of current level of function, identification of factors which may impact participation, conduct appropriate assessment, identification of strengths/barriers, generation of hypothesis, identification of outcomes, conduct intervention, analyze data, and monitor progress. Galheigo (2011) emphasizes that epistemic reflexivity is important to develop for the profession. This process at the macro-, meso-, and micro- scopic levels has begun to and should continue to occur in Brazil. A commonly accepted terminology and core definition of the profession within occupational therapy education, throughout provision of occupational therapy services, and with peer-reviewed dissemination of knowledge of social occupational therapy will successfully meet societal and individual needs of a 21st century Brazil. References BROWN, T. Journal quality metrics: options to consider other than impact factors. American Journal of Occupational Therapy, Rockville, v. 65, n. 3, p. 346-350, 2011. http://dx.doi.org/10.5014/ajot.2011.001396. EMMEL, M. L. G.; CRUZ, D. M. C.; FIGUEIREDO, M. An historical overview of the development of occupational therapy educational institutions in Brazil. South African Journal of Occupational Therapy, Pretoria, v. 45, n. 2,p. 63-67, 2015. http://dx.doi.org/10.17159/2310-3833/2015/v45n2a10. FREIRE, P. Pedagogy of the Oppressed. New York: Continuum, 2006. GALHEIGO, S. M. Occupational therapy in the social field. In: KRONENBERG, F.; POLLARD, N.; SAKELLARIOU,D. Occupational therapy without borders: towards an Ecology of occupation-based practices. London: Churchill Livingstone, 2011. p. 48-56. GUTMAN, S. A. State of the Journal. American Journal of Occupational Therapy, Rockville, v. 64, n. 6, p. 832-840, 2010. http://dx.doi.org/10.5014/ajot.2010.064601. HOOPER, B. et al. Value and challenges of research on health professions’ core subjects in education. Journal of Allied Health, Washington, v. 43, n. 4, p. 187-193, 2014. LOPES, R. E.; HAHN, M. S. The education of occupational therapists in Brazil: history and perspectives. World Federation of Occupational Therapists Bulletin, England, v. 49, n. 1, p. 24-32, 2004. http://dx.doi.org/10.1179/otb.2004.49.1.007. LOPES, R. E. et al. Occupational therapy professional education and research in the social field. World Federation of Occupational Therapists Bulletin, England, v. 66, n. 1, p. 52-57, 2012. http://dx.doi.org/10.1179/otb.2012.66.1.021. MAGALHÃES, L.; GALHEIGO, S. M. Enabling international communication among Brazilian occupational therapists: seeking consensus on occupational terminology. Occupational Therapy International, Hoboken, v. 17, n. 3, p. 113-124, 2010. http://dx.doi.org/10.1002/oti.292. MALFITANO, A. P. S. et al. Social occupational therapy: conversations about a Brazilian experience. Canadian Journal of Occupational Therapy, Thousand Oaks, v. 81, n. 5, p. 298-307, 2014. http://dx.doi.org/10.1177/0008417414536712. MCINERNEY, C. A. et al. Programa Integrando: applications of the occupational therapy practice framework in Brazil. World Federation of Occupational Therapists Bulletin, England, v. 55, n. 1, p. 34-41, 2007. http://dx.doi. org/10.1179/otb.2007.55.1.006. SCHAAF, R. C. Creating evidence for practice using data-driven decision making. American Journal of Occupational Therapy, Rockville, v. 69, n. 2, p. 1-6, 2015. http://dx.doi.org/10.5014/ajot.2015.010561.